2021
DOI: 10.3389/fbioe.2021.611837
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxia Onset in Mesenchymal Stem Cell Spheroids: Monitoring With Hypoxia Reporter Cells

Abstract: The therapeutic and differentiation potential of human mesenchymal stems cells (hMSCs) makes these cells a promising candidate for cellular therapies and tissue engineering. On the path of a successful medical application of hMSC, the cultivation of cells in a three-dimensional (3D) environment was a landmark for the transition from simple two-dimensional (2D) testing platforms to complex systems that mimic physiological in vivo conditions and can improve hMSC curative potential as well as survival after impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…In the present study, MSC spheroids that were assembled by 40,000 cells and cultivated for 2 days with a diameter of approximately 525 µm showed the best therapeutic potential. The discrimination between the investigated groups was thought to be attributed to the difference in the intrinsic gradients of oxygen, nutrients and signal molecules present in the spheroids [39,40]. Typically, as the spheroid size increases, the limited availability of oxygen owing to the increased diffusion distance is considered to mainly account for the development of a hypoxic core in spheroids, thereby altering cellular behaviors or even causing the death of interior cells [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, MSC spheroids that were assembled by 40,000 cells and cultivated for 2 days with a diameter of approximately 525 µm showed the best therapeutic potential. The discrimination between the investigated groups was thought to be attributed to the difference in the intrinsic gradients of oxygen, nutrients and signal molecules present in the spheroids [39,40]. Typically, as the spheroid size increases, the limited availability of oxygen owing to the increased diffusion distance is considered to mainly account for the development of a hypoxic core in spheroids, thereby altering cellular behaviors or even causing the death of interior cells [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Even tough, from a clinical perspective, a substantial cell density is required for cell-based therapies to trigger tissue formation, the increasing length of nutrient transport by diffusion arises as a limitation. While Schmitz et al showed that MSC spheroids with diameters greater than 200 µm are vulnerable to hypoxia and implicitly cell death [33] several other studies inves-tigated the presence of a hypoxic core by means of histological approaches and indicated the presence of proliferating cells in spheroids up to 1000 µm in diameter [29,34,35]. It has to be borne in mind that in a clinical context, for peripheral arterial disease, the spheroidal size has to be subjected to further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…By establishing spheroid culture, more cells can be obtained than by monolayer cultures [182], therefore secreted factors amount increases together with an enhancement in anti-inflammatory factors production [183]. In stem cell spheroids the relative hypoxia located at the center of the sphere has a critical role [184] in the maintenance of stemness and for clinical application of MSCs [185]. Protein synthesis and cell volume increase can be uncoupled [186].…”
Section: Microfluidic Tools For Biophysical Selection Of Mscsmentioning
confidence: 99%